Are Market GM Plants an Unrecognized Platform for Bioterrorism and Biocrime? - Mueller, Siguna (Frontiers in Bioengineering and Biotechnology, 2019)
Existing classifications of potential biological weapons can only acknowledge a limited number of parameters of risk-potential. This has led to various classification scores based on risk and clinical manifestation, and a detailed list of potential bioterrorism agents. Yet, it is argued here, one critical factor has been overlooked. Biological mediums are information carriers similar to - and far more complex than - cyber-digital carriers such as computers and the internet. Recent analyzes and experiments (\cite{Ney2017,peccoud2018cyberbiosecurity}) have confirmed attack possibilities from both sides of these carriers of information. Hence, it is suggested here that analogs of conventional cyber-hacking tricks can lead to new forms of bioterrorism and biocrime. Thereby, novel technologies can be misused to clandestinely exchange GM plants already on the market. While several risk scenarios involving GMOs - such as antibiotic resistant pathogens, synthetic biology, or mixing of non-GMO seeds with GMO seeds - have previously have been recognized, the new vulnerability adds another dimensionality - that of intentionality manipulating GMOs to create damage. The danger of actively inflicting diseases on plants may pose serious health hazards to both humans and animals, have detrimental consequences to the economy, and directly threaten the food supply. As this is the first study of this kind, the full scope and impact of suck attacks - especially those involving the intended misuse of technologies such as gene-drives - merits further investigation. Herein, the plausibility of these new risks will be demonstrated by, (1) Highlighting ownership and origination issues (esp. of event-specific GM-plants) as unrecognized risk factors; (2) Drawing parallels from cryptography and investigating the unique role of GM-plants, why - and how - certified GMOs could become a new venue for such attacks; (3) Analyzing previously unrecognized dual-use potentials of modern technologies and - paradoxically - research that is oriented towards the advancement of GMOs and plants. The potential of certified GM plants for bioterrorist attacks is real, because of the lack of awareness of such risks, due to practical challenges relative to tracking and authentication, and as they can be (genetically) manipulated without anyone's knowledge of the Trojan horse hidden inside.